2017
DOI: 10.1155/2017/1401452
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Specific Redox Biomarkers and Age in a Large European Cohort: The MARK‐AGE Project

Abstract: Oxidative stress and antioxidants play a role in age-related diseases and in the aging process. We here present data on protein carbonyls, 3-nitrotyrosine, malondialdehyde, and cellular and plasma antioxidants (glutathione, cysteine, ascorbic acid, uric acid, α-tocopherol, and lycopene) and their relation with age in the European multicenter study MARK-AGE. To avoid confounding, only data from countries which recruited subjects from all three study groups (five of eight centers) and only participants aged ≥55 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 52 publications
5
37
1
Order By: Relevance
“…In our study, we observed that Alu methylation at the CpG1 site do not display marked age-related changes, but lower levels of methylation at this site were found in elderly subjects over 65 years compared to the age class 55-64 years. Regarding the other CpGs, we observed only a significant increase in the 55-64 years age class compared to the youngest age class (35)(36)(37)(38)(39)(40)(41)(42)(43)(44). This last finding would appear to be in contrast with previous results, where young subjects have higher Alu methylation levels than older ones [18].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In our study, we observed that Alu methylation at the CpG1 site do not display marked age-related changes, but lower levels of methylation at this site were found in elderly subjects over 65 years compared to the age class 55-64 years. Regarding the other CpGs, we observed only a significant increase in the 55-64 years age class compared to the youngest age class (35)(36)(37)(38)(39)(40)(41)(42)(43)(44). This last finding would appear to be in contrast with previous results, where young subjects have higher Alu methylation levels than older ones [18].…”
Section: Discussioncontrasting
confidence: 99%
“…Total glutathione and total free cysteine in whole blood were measured by RP-HPLC with UV-Vis detection after reduction and modifications as previously reported [37].…”
Section: Determination Of Total Glutathione and Total Free Cysteine Imentioning
confidence: 99%
See 1 more Smart Citation
“…Several assays are available for measuring ROS generation, antioxidant defense, and oxidative damage to macromolecules in blood, cells, and tissues (Dikalov & Harrison, 2014;Starkov, 2010). The significance of these oxidative stress biomarkers for aging is uncertain, as in many cases they have been studies in specific medical conditions and not in the context of aging studies (Al Shahrani, Heales, Hargreaves, & Orford, 2017;Hayashi & Cortopassi, 2015;Weber et al, 2017). Studies that use multiple mitochondrial biomarkers have revealed only a slight intercorrelation between the markers and aging, suggesting that they tap into different biological dimensions (Lara et al, 2015;Larsen et al, 2012;Marrocco, Altieri, & Peluso, 2017;Xia, Chen, McDermott, & Han, 2017).…”
Section: Mitochondrial Functionmentioning
confidence: 99%
“…Differences between RASIG and the other two groups, with no differences between GO and SGO, could be lifestyle-related while differences between GO and SGO (irrespective of the RASIG results) suggest a genetic contribution. The levels of redox biomarkers, such as protein carbonyls, 3-nitrotyrosine, malondialdehyde, and cellular and plasma antioxidants (glutathione, cysteine, ascorbic acid, uric acid, α-tocopherol, and lycopene) were analyzed and compared within the three different subgroups (Weber et al, 2017):…”
Section: Oxidative Stress Biomarkersmentioning
confidence: 99%